Peran Intelijen Polres Bungo dalam Pengamanan Pemilihan Rio Serentak Kabupaten Bungo - Ronal Dison; Harwan dolly (Universitas Muara Bungo, 2023)
The location of this research was carried out at the PMD Service Office, the Bungo Police Intelligence and Security Unit Office and in several hamlets that held Rio elections simultaneously in Bungo Regency. This research was carried out for 1 month, namely from 01 February to 10 March 2023. The research aims to determine the performance evaluation of the Political Unit of the Intelligence and Security Unit of the Bungo Police in the Implementation of Simultaneous Elections in Bungo Regency in 2022 and to analyze the factors inhibiting and supporting the evaluation of the Unit's performance Politics of the Bungo Police Intelligence and Security Unit in the Implementation of Simultaneous Elections in Bungo Regency in 2022. This research uses qualitative methods. The results of the research show that the Performance Evaluation of the Political Unit of the Intelligence and Security Unit of the Bungo Police in Organizing Simultaneous Rio Elections in Bungo Regency in 2022 is: 1) Evaluation of the Performance of the Political Unit of the Intelligence and Security Unit, 2) Evaluation of the performance of the Rio Election Committee in Communication, 3) Evaluation of the Performance of the Political Unit of the Intelligence and Security Unit, 2) Evaluation of the performance of the Rio Election Committee in Communication, 3) Evaluation of Human Resources and 4) Evaluation of the Operational budget and Inhibiting and Supporting Factors for the Performance of the Political Unit of the Bungo Police Intelligence and Security Unit in Holding Simultaneous Rio Elections in Bungo Regency in 2022, namely: a. Inhibiting factors are: Lack of Human Resources for the Executive Committee, Lack of Operational Budget, Short Stage Time. b. Supporting Factors are; There is a legal basis, there is budget support. c. There is synergy between the Political Intelligence and Security Unit and the PMD Service.